1971
DOI: 10.1037/h0031305
|View full text |Cite
|
Sign up to set email alerts
|

Humor, anxiety, and task performance.

Abstract: Subjects differing in level of test anxiety were administered a course examination under standard classroom conditions. Approximately half of the subjects received a form of the examination containing one-third humorous test items, while the remainder of the subjects received a nonhumorous form of the examination. High-test-anxious subjects receiving the nonhumorous form performed significantly more poorly than did low-or moderate-test-anxious subjects, and at a significantly lower level than did the high-anxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1

Year Published

1975
1975
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(28 citation statements)
references
References 10 publications
2
25
1
Order By: Relevance
“…These students tended to be already highly motivated to do well in statistics or already have a high level of interest in the subject. A similar outcome was observed when the inclusion of humor during an examination was studied by Smith et al (1971). It was found that humor enhanced the recall of information among students with high anxiety.…”
Section: Conclusion On the Use Of Humor In Teaching Statisticssupporting
confidence: 61%
See 1 more Smart Citation
“…These students tended to be already highly motivated to do well in statistics or already have a high level of interest in the subject. A similar outcome was observed when the inclusion of humor during an examination was studied by Smith et al (1971). It was found that humor enhanced the recall of information among students with high anxiety.…”
Section: Conclusion On the Use Of Humor In Teaching Statisticssupporting
confidence: 61%
“…Torok, McMorris, and Lin (2004) found that students report that they are less supportive of using humor on tests than in class. However, an experimental study found that humor may facilitate performance in high anxious students when it is included on examinations (Smith, Ascough, Ettinger and Nelson, 1971).…”
Section: When To Use Humor In the Statistics Classroommentioning
confidence: 99%
“…Thus, the third graders were initially less tense than the fifth graders; in fact, initially the third graders could have been below, and the fifth graders above, the optimum level of tension for effective performance. Instructions deemphasizing the importance of the test would have reduced arousal in all students (Sarason, Mandler, and Craighill, 1952), and the humor manipulations would have further reduced the Humor students' tension (Smith, et al, 1971). If the third graders were initially low in arousal, continued reductions in tension would be manifested in lower performance, and if fifth graders were relatively high, then reductions would at first be manifested in heightened performance (as the ontimum was approached) and then, with further tension reduction, lowered performance (as the optimum was passed).…”
Section: Resultsmentioning
confidence: 99%
“…It has long been recognized that there is an optimal level of tension for effective performance (Terry and Isaacson, 1971) ; ie., extremely high or low tension inhibits performance. Smith, et al (1971) showed that highly anxious students scored significantly higher on a humorous test than on a nonhumorous test, presumably because the humor reduced the high anxiety down to the optimal level. But they also report that students with lower anxiety tended to do more poorly on the humorous test than on the nonhumorous test, presumably because their anxiety was reduced to below the optimal level.…”
mentioning
confidence: 99%
“…While sense of humor is typically viewed as a personality trait, one might possess a sense of humor while not actually using humor in all interactions. Many scholars have indicated that humor serves a variety of functions (Chapman, 1983;Cheatwood, 1983;Civikly, 1983;Coser, 1960;Duncan, 1984;Foot, 1986;Malone, 1980;Poole, 1983;Smith, Ascough, Ettinger, & Nelson, 1971;Ziv, 1984Ziv, , 1988a. However, the independent functions have yet to be collapsed into a reliable and valid measure indicative of an individual's repertoire of humor motives or tendency to enact these motives.…”
Section: Spring 1992mentioning
confidence: 98%